Um bichinho me pegou: a escolha e a permanência no universo das corridas de rua - Karine Barbosa de Oliveira (2016)
The running in Brazil since 1979, is gaining more space in large urban centers, which the media show are not just a sport, but something that is becoming a "lifestyle". The running is constantly growing, especially in recent years, no regard to the number of practitioners, the number of tests carried out during the year and the increase in running groups, which are also known as sports advisors. These sports consultancies in running are specialized companies to meet their customers / students to practice the race, having fixed points of meetings with its own structure and organization who possess professional guidance in Physical Education. The running are physical activities performed in the leisure time of practitioners and have become a product in a growing market. In addition, we can say that runners have identities that bind them to other runners and form the tribe of runners. The running is influenced by culture, from breeding and production of gestures, customs, principles, rites, among others, that make up the identity of the practitioner, which form the tribe of runners. This work aimed to: investigate why the choice and remain in the running for belonging to running groups in the city of Belo Horizonte. Therefore, the work proposed to identify the reasons for the choice and stay in the running; identify the reasons for the practice of choosing the running with the support of advisory services; and also to identify the running is considered the practice of leisure through the halls. As methodological procedure was carried out a literature review on the themes: running, sociology of sport, culture, consumption and identity. The field survey was conducted via online questionnaire sent by e-mail, ten advisors who agreed to participate, and they headed for their students. We obtained 390 returns, with 179 women and 211 men, who have mostly aged 30 to 39 years old are married and have graduate. The main reason for choosing the running is due to ease of practice, and they remain the same reasons they entered and also added the issue of socialization as one of the most cited, or became the main reason for those who remain in the activity by other reasons. Most participants reported that the main reason for the choice of practicing in consultancies is looking for a professional orientation. Most participants also consider the running as leisure, in which the question of pleasure, socialization and relief of stress were identified as justification. We conclude that the issue identified as a reason for choice of activity remains, but there are other elements that add to the reasons of their stay and that running is a form of occupation of practicing leisure time who value the practice of running form oriented, which is offered by the advisory.